Epidemiological profile of SARS-CoV-2 infections in health professionals at a university hospital in the City of João Pessoa, State of Paraíba (PB), Brazil (Research, Society and Development, 2024)
The aim of this study is to identify the epidemiological profile of SARS-CoV-2 infections in health professionals at a University Hospital in João Pessoa – Paraíba, Brazil. This is an epidemiological research, clinical-laboratory, descriptive and quantitative. The cases of infection were obtained through laboratory confirmation using the technique of polymerase chain reaction in real time reverse transcription (RT-qPCR) in samples of nasopharyngeal secretions (SNF) and data from the investigation form of suspected flu syndrome by the 2019 Coronavirus. A total of 67 participants perfomed the exam. Of these, only 18 (26.8%) showed viral detection for SARS-CoV-2 by RT-qPCR. The most affected gender was female 12 (67%). The median age was 42 years old. The most prevalent symptom was headache 14 (31.1%). There were no cases of comorbidity. Female health professionals over the age of 30 constituted the largest proportion of study participants.